2018
DOI: 10.4314/ijbcs.v12i3.4
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of rubella-specific IgM and IgG antibodies among pregnant women in a Catholic Hospital in Yaoundé, Cameroon

Abstract: Rubella virus (RV) infection is responsible of an unresolved clinical complication that affects newborns and children. During the first trimester of pregnancy, it often causes severe birth defects known as congenital rubella syndrome (CRS). This study reports the seroprevalence of the RV-specific IgM and IgG antibodies, its relationship with the duration of pregnancy and past history of abortion in pregnant women at Yaoundé in order to help strategies to eliminate rubella and to prevent Congenital Rubella Synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(9 reference statements)
0
1
1
Order By: Relevance
“…Reports from various countries showed the prevalence of rubella among schoolgirls, pregnant women and women at productive age (child bearing age). [13][14][15][18][19][20][21][22] In the current study, there was no statistically significant difference between the rate of rubella virus antibodies and residence age, socioeconomic status, education levels, abortion time, congenital defects and symptoms. On the other hand, there was a significant between rubella IgG antibody and a previous number of abortions.…”
Section: Discussioncontrasting
confidence: 60%
“…Reports from various countries showed the prevalence of rubella among schoolgirls, pregnant women and women at productive age (child bearing age). [13][14][15][18][19][20][21][22] In the current study, there was no statistically significant difference between the rate of rubella virus antibodies and residence age, socioeconomic status, education levels, abortion time, congenital defects and symptoms. On the other hand, there was a significant between rubella IgG antibody and a previous number of abortions.…”
Section: Discussioncontrasting
confidence: 60%
“…Though not statistically evaluated, it is expected that prevalence rates will be less in rural than urban settings due to crowding [26]. Some studies in pregnant women from hospital settings in Nigeria and Cameroon have also shown low prevalence rates, 3.9, 5.0, 1.84, 1.25% [14,23,25,27], while others have reported relatively high rates 38.8%, and 16.3%, and 10.1% [9,28,29]. The high prevalence rates may be accounted for by possible outbreaks which may have resulted in both new and re-infections [9], the possibility of false positives should however not be discounted.…”
Section: Discussionmentioning
confidence: 99%